2017
DOI: 10.5152/tao.2017.2079
|View full text |Cite
|
Sign up to set email alerts
|

Benign Paroxysmal Positional Vertigo in Pregnancy

Abstract: Benign paroxysmal positional vertigo (BPPV ) is a clinical entity characterized by acute, brief paroxysmal attacks of rotational vertigo induced by head position changes. It is the most common peripheral vestibular pathology and is seen more frequently in women. However, to our knowledge, there is very limited data on the association between BPPV and pregnancy in both English and Turkish literature. We present four pregnant women diagnosed with BPPV for the first time during gestation and revise the etiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Although the link between BPPV and pregnancy is still unclear, some pregnant women have been first diagnosed with BPPV during pregnancy ( 47 ).…”
Section: Clinical Evidencementioning
confidence: 99%
“…Although the link between BPPV and pregnancy is still unclear, some pregnant women have been first diagnosed with BPPV during pregnancy ( 47 ).…”
Section: Clinical Evidencementioning
confidence: 99%
“…The prevalence of dizziness/ vertigo was reported to be 10-52% in the studies conducted on pregnancy. 3,18 In the study of Scmith et al on 82 pregnant women, vertigo was reported for more than half the pregnant women (52%). 3 Agampodi et al ( 2013) found that 24% of 466 pregnant women experienced dizziness.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, three of the four patients described, were diagnosed during the late gestational weeks, when sleeping and daily activities are usually restricted. They also suppose the usual attitude to sleep on their left sides as another risk factor for BPPV in pregnant women (24). Recently, there have been reports that calcium and vitamin D metabolism disorders are risk factors for BPPV.…”
Section: Discussionmentioning
confidence: 99%